Mining policy and environmental sustainability in Ecuador - Rea Toapanta, Antonio Ricardo (2017)
In today’s Ecuador, historically, in the provinces of Manabí and Esmeraldas on the Coast; Azuay and Cañar in the Sierra, were the most developed mining. In the decades of the 80s and 90s, the British Mission performed geological research in the Eastern (Real) and Western Ranges, concluding with the publication of maps at different scales. The competencies of the Sector Ministry are to exercise the rectory of the public policies of the geological-mining area, to issue the administrative agreements and resolutions that require their management; Evaluate policies, plans and projects for the development of the mining sector; Define, in coordination with the governing body of national planning, the National Development Plan for the Mining Sector. The Mining Law, in force since January 2009, estab-lished a new institutional structure, made up of: Sector Ministry (Ministry of NonRenewable Natural Resources), considering Artisanal Mining and Small-scale Mining. For 2012, Ecuador initiated large-scale mining activities. The Ecuadorian Government, through the National Secretariat for Planning and Development (SENPLADES), defined five strategic mining projects: Fruta del Norte, Mirador, Project awarded to the company Gold Gold, Río Blanco and Panantza San Carlos. Prior to their exploitation, concessionaires of these projects must sign a mining contract with the State. The environmental aspect considers: Direct or indirect impact on the environment. Depending on the effect; Short or long term. Be reversible or irreversible. The five projects, plus the Llurimagua project, located in Imbabura, should attract investments of about USD 8 billion up to 2024, presenting optimism for the mining industry, but the challenges are in mitigating environmental impacts and training productive labor.